The Application of SWOT Analysis to Improve Operational Efficiency in the Manufacturing Industry of PT. XYZ - Abdillah Wicaksono (Siber Nusantara of Economic and Finance Review, 2025)
This scientific article, titled "The Application of SWOT Analysis to Improve Operational Efficiency in the Manufacturing Industry of PT. XYZ", aims to analyze the implementation of the SWOT (Strengths, Weaknesses, Opportunities, Threats) method in enhancing operational efficiency at PT. XYZ, a leading automotive company in Indonesia. In the face of globalization and increasingly intense industrial competition, operational efficiency has become a key factor in maintaining the company’s competitiveness. Using a qualitative-descriptive approach, data were collected through observations, interviews, and internal documentation studies. The SWOT analysis results show that PT. XYZ's main strengths lie in its integrated production system and advanced technology, although it still faces weaknesses such as limited process flexibility and dependence on certain supply chains. Opportunities to enhance efficiency include process digitalization and human resource development, while threats come from global market fluctuations and technological advancements by competitors. The strategic recommendations derived from this analysis are expected to serve as a reference for managerial decision making to sustainably improve operational performance.